Análise experimental do reinício do escoamento de petróleo parafínico em tubulações - Rosso, Nezia de (2014)
In offshore production, pipelines are used to transport crude oil from the well bore to the platform and from the plataform to the seacoast. When production is interrupted for maintenance or emergency, waxy crude oils tend to form gel at seabed low temperatures. At flow start-up, an increase in pressure above the usual operating pressure is required to break the gel. The literature has reported that not only the temperature but also the cooling rate, the shear rate during cooling and the material aging time affect the gelation of waxy crude oils, and, therefore, the start-up pressure. The objective of the current work is to evaluate experimentally the start-up flow of waxy crude oils in pipelines. In order to accomplish that, an experimental lab loop was build to reproduce the flow start-up of gelled waxy crude oils. The loop allows the control of temperature, cooling rate, shear rate and aging time in the gel formation. The pressure peaks measured during the flow restart were presented and analized as a function of the controlled parameters. The research shows that all parameters tested have some influence on the picks of pressure during the start up flow of paraffinic oil gelled.